Trazodone modulates behavioral alterations in scopolamine-induced cognitive deficit by targeting brain-derived neurotropic factor and cAMP response element-binding protein signaling - Dhaka, Prashant; Pinky,; Neha,; Khan, Mohammad Ahmad; Rabbani, Syed Arman; El-Tanani, Mohamed; Parvez, Suhel (Frontiers in Cellular Neuroscience, 2026)
BackgroundTrazodone, an antidepressant, may play a potential role in enhancing long-term memory by combining anxious behavior deficits induced by scopolamine. The current study proposes the potential novel mechanistic insights between oxidative stress and memory biomarkers, including BNDF and CREB pathways, to modulate the pathogenesis of AD-like symptoms.MethodsBehavioral deficits were studied in terms of biochemical determination of lipid peroxidation and acetylcholinesterase activities. In addition, the study looked at the immunohistochemistry of BDNF and CREB against scopolamine-induced AD-like symptoms. Moreover, histopathological alterations were also performed against an AD-like model. Aβ42 proteins immunofluorescence was performed due to its known mechanism under AD. Finally, scopolamine-induced intraperitoneal mechanisms were studied in rats to establish an AD-like model.ResultsThe present study findings showed that administration of TRAZ considerably improved cognitive impairments as validated by NOR and display of anti-anxiety behavior, as verified by EPM. In addition, biochemical findings confirmed that TRAZ lowered oxidative stress through LPO, reduced Aβ deposition, and decreased the AChE. Furthermore, there was a notable upregulation of BDNF and CREB signaling expression, as confirmed by the IHC.ConclusionOverall, the study findings confirmed that TRAZ could be useful in mitigating the negative effects of scopolamine-induced cognitive impairment and lowering oxidative stress by enhancing memory indicators.